PENGARUH LIKUIDITAS OBLIGASI, JANGKA WAKTU JATUH TEMPO, DAN KUPON OBLIGASI TERHADAP PERUBAHAN HARGA OBLIGASI KORPORASI DENGAN RATING OBLIGASI SEBAGAI VARIABEL MODERATING PADA OBLIGASI KORPORASI DI BURSA EFEK INDONESIA. - Teti Indriyanti; Andewi Rokhmawati; Edyanus Herman Halim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to analyze the effect of Bond Liquidity (BL), Term Maturity (TM), Bond Coupon (BC) on Bond Price Changes are moderated by Bond Rating (BR). This reseacrh was conducted on companies that issue corporate bonds on the Indonesian Stock Exchange in year 2012 – 2015. This research uses the secondary data obtained from ICAMEL, IBPA, BEI. The total sample took as many as 33 corporate bonds, by using purposive sampling method. The method of processing data uses multiple regression analysis method and regression of moderation with SPSS version 21.0 Software. Based on the result of analysis showed that bond liquidity and term maturity have negative effect and significant to change of corporate bond price. The bond rating strengthens the effect of liquidity and maturity on changes in corporate bond prices. The bond coupon has no effect on changes in corporate bond prices and the bond rating does not moderate the bond coupon on changes in the price of corporate bonds.Keyword : Bond Liquidity, Term Maturity, Bond Coupon, Bond Price Changes, and Bond Rating